General characteristics of social work in the Crimea (in the second half of the nineteenth – early twentieth century) (Pedagogy of Higher and Secondary Education, 2013)
Simakova E. S. General characteristics of social work in the Crimea (in the second half of the nineteenth – early twentieth century)The article analyzes the state of knowledge about the problem of social work in Crimea from the second half of XIX century to the early XX century and as well it gives its general characteristics, i.e. the creation and functioning of social institutions. The author describes the main working directions of district councils, schools, orphanages, institutions of guardianship and custody for minor children.
Keywords: social work; minor children; social institutions in Crimea from the second half of XIX century to the early XX century